P14.48 Extracerebral relapses of primary CNS lymphoma (PCNSL): a LOC network retrospective study. (9th September 2021) - Dufour, J; Choquet, S; Schmitt, A; Ahle, G; Houot, R; Taillandier, L; Ursu, R; Hoang-Xuan, K; Soussain, C; Houillier, C
Abstract: BACKGROUND: Classically PCNSL remain confined within the CNS throughout their evolution for reasons still unknown (> 80% cerebral relapses). The aim of this study was to describe the characteristics and outcomes of the rare extracerebral relapses of PCNSL. MATERIAL AND METHODS: This is a multicenter, retrospective study. We included all immunocompetent patients newly diagnosed with diffuse large B-cell PCNSL registered in the national LOC network database since 2010 and followed prospectively, who presented an extracerebral relapse, pure (extracerebral only site) or associated with concomitant CNS relapse (mixed). All had body scan and/or TEP -CT at diagnosis work up. RESULTS: Of the 1968 PCNSL included in the database, 29 (1.5%) patients presented a systemic relapse [median age 71 years, median KPS 70% at relapse], either pure (n=19) or mixed (n=10), with a histological confirmation in 19 cases (66%). The median delay between initial diagnosis and systemic relapse was 15 months [2–49 months], with 5 very early relapses (<8 months) and 10 late relapses (>21 months). 27 patients had symptoms, 21 related to the location of relapse and 6 with only general symptoms. The localization was thoracic (n=11), abdominal/pelvic (n=14), head/neck (n=6) and limbs (n=9). We found visceral (n=24, 83%), including testis in 5 (28%) men and breast in 3 (27%) women, lymph node (n=12, 41%) and peripheral nervous system (PNS) (n=8, 28%; 4 plexus and 4 extradural roots) involvement. 27 patients were treated with chemotherapy, either with only systemic target (n=8) (R-CHOP alone) or mixed systemic and CNS target (n=19) (R-CHOP-MTX, R-ICE, GEMOX, RDHAC) and consolidated by high-dose chemotherapy with autologous stem cell transplantation (HCT-ASCT) in 4 cases [median age 55 years, median KPS 80%], with 34% of complete response. After systemic relapse, median progression-free survival was 8 months and overall survival (OS) was 9 months, 15 months for pure systemic and 4.5 months for mixed relapses. KPS>70%, pure systemic relapses and complete response were significantly associated with higher OS in univariate analysis. CONCLUSION: Extracerebral PCNSL relapses are very rare, mainly extranodal and involve a large spectrum of anatomical sites, the most frequent being testis, breast and PNS. Prognosis was worse in case of mixed relapse than in pure systemic relapse that was similar to non PCNSL lymphomas. Very early relapses raise the question of misdiagnosed occult extracerebral lymphoma at diagnostic work up that should include systematically a FDG PET-CT. More studies are needed to refine their treatment and to specify the role of HCT-ASCT. Paired tumor tissues at diagnosis (CNS)/relapse (extracerebral) analysis would provide a better understanding of underlying molecular mechanisms.